Quantification of Humic Acid Produced in Worm-Activated Cast and Soil under Varied Land Use Types in Raebareli District - Singh , Garima; Bhadauria, Tuneera (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2023)
The current study involves measuring the amount of humic acid produced by earthworms in their castings across five land uses, which were identified based on the level of anthropogenic activity along a disturbance gradient ranging from least disturbed protected forest to intensive agriculture to abandoned fallow to sodic ecosystem and then rehabilitated agroecosystem. Humic acids were recovered from typical soils and earthworm casts using the conventional alkali/acid fractionation method. According to the findings, humic acid obtained by casting has a significant advantage over humic acid derived from soil, which was directly impacted by the types of land use under consideration.